The Effectiveness Of Health Education On Public Perception and Knowledge Regarding The Use Of Garlic Extract To Lower Cholesterol in Suco Seloi Malere Aldeia Namanei Posto Administrativo Aileu Municipiu Aileu in 2024 - Leny Blegur; Rahaju Ningtyas; Maria Goreti Owa; Novio De Almeida Pereira; Yoseph Uli Yanto; Gonzalo Jose Texeira (International Journal of Health and Medicine, 2025)
This study aims to evaluate effectiveness of health education on public perception and knowledge regarding the use of garlic extract to reduce cholesterol in Suco Seloi Malere Aldeia Namanei Posto Administrativo Aileu Municipiu Aileu in 2024. This research uses a quasi-experimental design with a pretest-posttest approach. Data was collected from the community in Suco Seloi Malere Aldeia Namanei Posto Administrativo Aileu Municipiu Aileu in 2024 through questionnaires before and after being given health education. Before education, 62% of respondents had moderate knowledge; After education, 64% of respondents had high knowledge about the use of garlic extract to lower cholesterol. Before education, 60% of respondents had a moderate perception; After education, 62% of respondents showed an increase in perception to high perception. Before education, 38% of respondents had little experience, after education, 98% of respondents had good experience regarding the use of garlic extract to lower cholesterol. Before education, the majority of respondents (60%) had a secondary education level. After education, the proportion of respondents with a secondary education level remained stable at 60%. Before education, 40% of respondents felt a high cultural influence regarding the use of garlic extract. After education, this figure increases to 70%. The health education provided is effective in increasing public knowledge and perception regarding the use of garlic extract to lower cholesterol.